Analysis of the Hajj Fund Management Based on the Fatwa of the National Sharia Council (DSN) Number 122 Concerning the Management of BPIH Fund and Special BPIH Based on Sharia Principles - Ilham Maulid; Amirsyah Amirsyah (ADI Journal on Recent Innovation, 2021)
Badan Pengelola Keuangan Haji (BPKH) has the full authority to manage the existing Haj pilgrimage funds. However, the current issue is how to oversee the management of the Haj pilgrimage funds, which have crossed 100 trillion The monitoring of these funds management is not simple, particularly because the source of the funds comes from the ummah, where it belongs to the ummah, especially the pilgrims, and the benefits should be returned to the pilgrims representing the ummah and also for the benefit of the people and nation. This study aims to describe the fatwa of the National Shariah Board No. 122 concerning Funds Management of BPIH and Special BPIH based on Sharia Principles and to analyze whether the management of Hajj Pilgrimage Funding Costs (BPIH) is under the fatwa. This research used qualitative data. The research that produces descriptive data in the form of non-numeric data, which is a symptom, data information, based on facts obtained from the field, then conclusions are drawn. The result showed that the management of the hajj Pilgrimage Cost (BPIH) was by following the DSN-MUI fatwa. The suitability of Sharia in the management of hajj funds can be seen from the government transferring these funds to the halal sector as confirmed in the Law no. 34 of 2014 emphasizes that the management of hajj funds must comply with sharia principles, namely the sector that is avoided from maisir, gharar, usury, and other.